Maize Stalk Lodging: Morphological Determinants of Stalk Strength. Issue 2 (16th February 2017) - Robertson, Daniel J.; Julias, Margaret; Lee, Shien Yang; Cook, Douglas D.
Abstract : An incomplete understanding of stalk strength and stalk lodging impedes efforts to improve maize ( Zea mays L.) production. To develop a more complete understanding of stalk strength, the current study examined the effect of stalk morphology on stalk bending strength. A detailed geometric analysis was conducted on five varieties of dent corn sown at five planting densities in two replicates at each of two locations near Greenville, IA, in 2013. Stalks were imaged using high‐resolution X‐ray computed tomography, and morphological features of the stalk were quantified using customized computer code. After scanning, stalks were subjected to mechanical tests to determine stalk bending strength and rind penetration resistance. The section modulus of the stalk (a morphological quantity derived from engineering beam theory) was found to be highly predictive of stalk strength, and its predictions appear to be largely unaffected by common confounding factors such as hybrid and planting density. By assuming the stalk cross section to be a hollow ellipse, the section modulus of the stalk can be estimated using measurements of stalk diameter and rind thickness (which does not require computerized tomography scanning). The elliptical section modulus is highly predictive of stalk strength, does not appear to be confounded by experimental variables, and can be obtained using a pair of calipers. Thus, it demonstrates potential as a selective breeding index to improve lodging resistance. In the current study, the elliptical section modulus predicted stalk strength with four times the accuracy of rind penetration resistance (a more common method used in breeding studies).